The art of pain: A quantitative color analysis of the self-portraits of Frida Kahlo - Turkheimer, Federico E.; Liu, Jingyi; Fagerholm, Erik D.; Dazzan, Paola; Loggia, Marco L.; Bettelheim, Eric (Frontiers in Human Neuroscience, 2022)
Frida Kahlo (1907-1954) was a Mexican artist who is remembered for her self-portraits, pain and passion, and bold, vibrant colours. This work aims to use her life story and her artistic production in a longitudinal study to examine with quantitative tools the effects of physical and emotional pain (rage) on artistic expression. Kahlo suffered from polio as a child, was involved in a bus accident as a teenager where she suffered multiple fractures of her spine and had 30 operations throughout her lifetime. She also had a tempestuous relationship with her painter husband, Diego Rivera. Her physical and personal troubles however became the texture of her vivid visual vocabulary — usually expressed through the depiction of Mexican and indigenous culture or the female experience and form. We applied colour analysis to a series of Frida’s self-portraits and revealed a very strong association of physical pain and emotional rage with low wavelength colours (red and yellow), indicating that the expression of her ailments was, consciously or not, achieved by increasing the perceived luminance of the canvas. Further quantitative analysis that used the fractal dimension identified “The broken column” as the portrait with higher compositional complexity, which matches previous critical acclaim of this portrait as the climax of her art. These results confirm the ability of colour analysis to extract emotional and cognitive features from artistic work. We suggest that these tools could be used as markers to support artistic and creative interventions in mental health.